Clinical Significance and Immune Landscape of Recurrence-Associated Ferroptosis Signature in Early-Stage Lung Adenocarcinoma - Yi, Lilan; Huang, Ping; Gu, Yinfang; Wu, Guowu; Zou, Xiaofang; Guo, Longhua; Wen, Chunling; Zhu, Junlin; Zhao, Dongdong (Frontiers in Oncology, 2022)
Background: The prevalence of patients newly diagnosed with early-stage lung adenocarcinoma (LUAD) is growing alongside significant advances in screening approaches. This study aimed to construct ferroptosis-related gene score (FRGscore) for predicting recurrence, explore immune-molecular characteristics and determine the benefit of immunotherapy in distinct ferroptosis-based patterns and FRGscore-defined subgroups. Methods: A total of 1085 early-stage LUAD patients from four independent cohorts were included. Consensus clustering analysis was performed using 217 co-expressed FRGs to explore different ferroptosis-mediated patterns. A FRG scoring system was established to predict relapse, quantify ferroptosis-mediated patterns and evaluate the response to immunotherapy in individual patients based on Lasso-penalized and stepwise Cox regression analyses. Immune landscape involving multiple parameters was further evaluated, stratified by cluster subtypes and FRGscore subgroups. Results: Two ferroptosis-mediated patterns were identified and verified, which were characterized by significantly distinct prognosis and immune profiles. Analyses of immune characteristics showed that identified ferroptosis patterns were characterized as immune-inflamed phenotype and immune-exhausted phenotype, respectively. The FRG scoring model based on 11 FRG-derived signatures panel classified patients into FRGscore-high and FRGscore-low subgroups. Significantly longer recurrence-free survival (RFS) and overall survival (OS) were observed in FRGscore-low subgroup. FRGscore-low patients were characterized by higher TMB, immunoscore, immunophenoscore and PD-L1 expression level, and was associated with lower TIDE score, whereas the opposite was observed in FRGscore-high patients. Immune-active pathways were remarkably enriched in FRGscore-low subgroup. This scoring model remained highly predictive of prognosis across different clinical, molecular and immune subgroups. Further analysis indicated that FRGscore-low patients exhibited higher response to anti-PD-1/PD-L1 immunotherapy and better clinical benefits based on two independent immunotherapy cohorts. Conclusion: The proposed FRGscore could highly distinguish the recurrence patterns and molecular and immune characteristics, and predict immunotherapy prognosis, potentially representing a powerful prognostic tool for further optimization of individuated treatment and management strategies in early-stage LUAD.